LIQUID GASES TRANSMISSION MEDIUM TOZALOVCHI INERTIAL HYDRODYNAMIC SCRUBBER - Ergashev Nasimbek Akhmadjonovich; Isomidinov Azizjon Salomidinovich; Siddikov Rasuljon Uktamovich; Ummatov Rustambek Bektoshevich; Madaliyev Akhrorbek Niizonidin ogli (American Journals, 2022)
The article presents the theoretical research work carried out on determining the hydraulic resistance and resistance coefficient in the working bodies of the scrubber that washes the industrial secondary waste gases. The equation for determining the total hydraulic resistance of the scrubber is formulated, and the equations for determining the hydraulic resistance and resistance coefficient of each working body are proposed.
Keywords: hydraulic resistance, pipe, guide pipe, conical plug, grid nozzle